CEP-stable generation of close to single-cycle and ultrashort UV pulses at 800 kHz repetition rate using a gas-filled hollow-core PCF - Ermolov, Alexey; Heide, Christian; Dienstbier, Philip; Tani, Francesco; Köttig, Felix; Hommelhoff, Peter; Russell, Philip St. John (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ultrashort laser pulses at high repetition rates are a fundamental tool in a wide range of applications in strong-field physics and attosecond science, where particular attention has to be given to the stability of the carrier to envelope phase (CEP) of the ultrashort optical waveform [1]. Here we report the generation of close to single-cycle pulses with stable CEP at 800 kHz repetition rate, obtained via soliton-effect self-compression in a gas-filled kagomé-type hollow-core photonic crystal fibre (kagomé-PCF) [2]. In addition, we have measured for the first time the CEP stability of soliton-emitted dispersive waves (DWs) lying in the ultraviolet spectral region.
CRIS-Team Scopus Importer:2019-11-15